In Vitro Production and Transfer of Buffalo Embryos (Bubalus bubalis) in Argentina - Bandeo, A.; Konrad, J.L.; Ponce, P.; Vallejos, N.; Sansinena, M.; Berdugo, J.; Crudeli, G.; Vargas, P. Maldonado (Journal of Buffalo Science, 2025)
Objective: This study aimed to evaluate different hormonal stimulation protocols over follicular development, oocyte quality, embryo production, and embryo transfer outcome. Methods and Materials: This study was performed in Argentina. Fifty-three non-pregnant females with proven fertility and good body condition were selected to produce embryos in vitro. Three ovarian stimulation protocols were tested: On Day 0, animals received a progesterone intravaginal device plus Estradiol Benzoate. On Day 4: TRT1 did not receive any treatment, TRT2 FSH (Folltropin-V®), TRT3 recombinant eCG (FoliRec®) TRT 4 serum eCG (Ecegon®), on day 7 oocyte retrieval was performed using ultrasonography. Embryos were produced, vitrified, and transferred to synchronized recipients using standard protocols. The number and quality of oocytes, number and size of follicles, embryo production, pregnancy rates, and Antimullerian hormone (AMH) levels were determined. Quantitative variables were compared, and an α level of 5% was considered significant. Results: The total number of oocytes, follicles, and zygotes did not differ across the treatments. Better oocytes were obtained in TRT2 and TRT4 (p<0.05). Embryo production was highest in TRT2 (1.5 embryos/buffalo/OPU), and cleavage was higher in TRT3 (p<0.05). Forty-two embryos were transferred, and 12 live births were obtained. All were males. Conclusions: The stimulation protocols used before OPU don’t improve the number of ovarian follicles; some treatments produce higher-quality oocytes and embryo production. AMH dosage can help in selecting animals to increase the efficiency of IVEP. Reasonable results were obtained from the transfer of vitrified embryos, and the subsequent birth of live animals demonstrates the viability of this technique.